The use of heated models to describe the thermal environment in shelters for farm animals - Pyykkönen, Markus (Agricultural and Food Science, 1992)
The dry bulb air temperature is still the most commonly used parameter to characterize the thermal environment, even though it disregards the effect of air velocity and the thermal properties of the flooring material on the heat loss from the animal. Measurements in the laboratory confirmed that an uninsulated heated model with an overall thermal resistance of 0.11 m 2 KW-1 is sensitive enough to differentiate between changes in conduction, convection and radiation conditions. Measurements on farms showed that the heat loss simulated by mechanical models gives a more diversified description of the thermal environment than the dry bulb air temperature. Although the uninsulated mechanical model is not a standardized device, it is a useful method for measuring the thermalenvironment especially under sheltered winter conditions.